Hemodynamic phenomena in retrobulbar and eyeball vessels - Modrzejewska, Monika (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The purpose of this review was to evaluate factors connected with blood flow and indices regulating vascular diameter and some parameters influencing retrobulbar circulation such as type of vascular resistance, anatomical structure of vascular wall and vessel lumen. Neurogenic and angiogenic factors, rheological blood composition, presence of anatomical and pathological obstructions on blood flow pathway as well as degree of development of collateral circulation pathways – have influence on the volume and blood flow velocity in eyeball. There were discussed bulbar circulation hemodynamics, emphasizing the importance of perfusion pressure. The role of risk factors was underlined for pathological lesions in vessels supplying blood to eyeball and in ophthalmic artery (OA) and its collaterals, in central retinal artery (CRA) as well as posterior ciliary arteries (PCAs), and in venous system carrying away blood from eye. In conclusion – the results of many studies of retrobulbar blood flow in different types of ophthalmic diseases of the vascular etiopathogenesis indicate that registry of the mean values of blood flow parameters and vascular resistance indices parallel to measurement of blood flow spectrum in OA, CRA, PCAs arteries, might contribute much information to explain or to evaluate nature of pathological changes in retinal and choroidal circulation.